How COVID-19 Pandemic Is Accelerating the Transformation of Higher Education Institutes: A Health Belief Model View - Ali Al-Tahitah; Ali Nasser Al-Tahitah; Mohammed Abdulrab (Springer, 2024)
Indexed by Scopus